HUBUNGAN ANTARA ASUPAN ZAT GIZI ENERGI, PROTEIN, ZAT BESI DAN POLA MENSTRUASI DENGAN KEJADIAN ANEMIA PADA REMAJA PUTRI BERDASARKAN JENJANG PENDIDIKAN DI KABUPATEN KEBUMEN - Agustina, Ely Eko (Bidan Prada, 2017)
Bleeding as a major cause of high maternal mortality rate in Indonesia begins with anemia.The prevalence of anemia was found different in other countries.Adolescence is a vulnerable age group to anemic. Anemia in adolescence girls will have an impact on reproductive health. The purposeof this study to determine the relationship between the intake of energy nutrients, iron proteinm and menstrual pattern with the incidence of anemia in adolescent girls in Kebumen regency in 2016. This research is an analytic observational with case control design.The sample in this study of 120 respondents.The study was conducted in May-June 2016. Data were collected by questionnaire instruments and Semi Quantitative- Food Frequency Quotionare (SQ-FFQ).Data analysis included univariate analysis of the frequency distribution of research variables, bivariate analysis withchi_square test, and multivariate logistic regression analysis. The results showed that there was a significant relationship between energy intake of p = (0.047), protein p = (0,000), iron p = (0.002), menstrual pattern p = (0.001) with anemia incidence in adolescent girls. Multivariate analysis of logistic regression showed the most dominant variable on the occurrence of anemia was protein nutrient intake of OR 4.255 in CI (1,850-9,784). Kebumen District Health Office needs to socialize School Intensive Nutrition Program intensively and comprehensively to reduce the incidence of adolescent anemia. The activities of socialization and provision of iron supplementation should be carried out continuously with good evaluation after implementation. Keywords: Anemia, Adolescence Girl, Nutrient Intake, Menstrual Pattern